Faktor-Faktor Penggerak Tax Avoidance pada Perusahaan Sektor Properti dan Real Estate di BEI : Konservatisme Akuntansi, Intensitas Modal dan Intensitas Persediaan - Julian Muhammad Hasan; Liana Dwi Septiningrum (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Tax avoidance is a significant concern for governments and regulators, particularly in sectors with substantial financial complexities such as property and real estate. This study aims to empirically investigate the influence of accounting conservatism, capital intensity, and inventory intensity on tax avoidance practices within property and real estate companies listed on the Indonesia Stock Exchange between 2018 and 2022. Using a quantitative descriptive approach and purposive sampling, the study analyzed 65 financial reports. Multiple linear regression analysis was performed using Eviews Version 12 to examine the relationships among the variables. The findings indicate that accounting conservatism, capital intensity, and inventory intensity collectively affect tax avoidance behaviors. However, when analyzed individually, accounting conservatism does not significantly influence tax avoidance, while both capital intensity and inventory intensity show a significant impact. These results suggest that companies with higher capital and inventory intensity may have more opportunities or incentives to engage in tax avoidance. The study highlights the need for regulators and policymakers to consider industry-specific characteristics such as asset structure when designing tax compliance frameworks. Furthermore, the findings contribute to the understanding of how financial reporting policies and operational factors relate to tax avoidance, offering valuable insights for investors, auditors, and tax authorities.